Communication as a Key Element in the Labor Inclusion of Mexican Millennials - Flor Madrigal-Moreno; Salvador Madrigal-Moreno; MarÃa de JeÃºs Montoya-Robles (International Review of Management and Marketing, 2020)
This research paper presents the situation of the labor market in Mexico, the behavior of organizations through their managers to integrate work teams, as well as the elements that stand out for being the most reasonable for the integration of millennials in the work force. On the other hand, the distinctive characteristics of this generational group are analyzed in search of communicative elements that favor their insertion in new organizations. The importance of communication, the favorable organizational climate through psychological contracts that improve and define the labor expectations of both parties (employer and millennials) are highlighted. The findings of this research allow identifying various communication problems between employers and millennials, mainly due to various inconsistencies between the expectations of each group.